Vulnerability and health risks of refugees, internally displaced persons: strategies of meeting their needs for sustainable development (2016)
Human displacement in form of internal displacement and refugee has become a nightmare to the global community’s unfolding events in the middle East and Africa leading to increase in the number of internally displaced persons (IDPs) and refugees in the world. The influx of refugees and IDPs presented the problems and challenges of management of refugees and internally displaced persons to the African governments and heads of states which necessitated the intervention of United Nations High Commission on Refugees to take over the management of refugees in West African sub-region. This however has not been able to address the humanitarian crisis posed by the escalating figures of refugees and internally displaced persons. This paper therefore attempted a holistic analysis of refugees and I DPs phenomenon globally with focus on West Africa and Nigeria with emphasis on conceptual clarification of refugees and IDPs, factors responsible for displacement, vulnerabilities of the displaced people, and response plan to manage humanitarian crisis occasioned by the phenomenon of refugees and IDPs.